Pendampingan Pembuatan Mykunas (Gummy Kulit Nanas) dalam Rangka Pemanfaatan Limbah Kulit Nanas di Pekon Gunung Terang, Kecamatan Bulok, Kabupaten Tanggamus Provinsi Lampung: Assistance in Making Mykunas (Pineapple Peel Gummy) in the Context of Utilizing Pineapple Peel Waste in Pekon Gunung Terang, Bulok District, Tanggamus Regency, Lampung Province - Afriyani, Afriyani; Ulandari, Atri Sri; Oktoba, Zulpakor; Suri, Nurma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Utilization of Pineapple Peel (Ananas comosus L.) waste into jelly candy products for dental health. This PKM activity aims to socialize the Farmer Group community that pineapple peels can be utilized and processed into gummy candy, which is effective in improving dental health. Pineapple skin is rich in bromelain, vitamin C, cysteine protease, and phytochemical compounds in the form of alkaloids, phenols, tannins, flavonoids, saponins, and carbohydrates. Pineapple skin also contains a rich source of vitamin C and manganese, which can help fight inflammation in the gums and tissues. Manganese helps in the development, strengthening, and repair of bones and teeth. Bromelain and Vitamin C in pineapple skin have the potential to be developed into pharmaceutical products. The method used is focus group discussion (FGD) by presenting theory in lectures, completing pre-test and post-test questionnaires, and interactive questions and answers. The results of the analysis based on the results of the pre-test and post-test questionnaires showed that there was a slight increase in participants' understanding after taking the test. The average percentage of participants' pre-test was 78.12%, while the average percentage of post-test was 78.33%. Utilizing pineapple peel waste in gummy candy is effective in improving dental health and opening up business opportunities for the community. Pineapple skin, which is rich in bromelain and vitamin C, has not previously been utilized optimally. With this assistance, the Pekon Gunung Terang community can process pineapple peel waste into products that are valuable and beneficial for health and the local economy.